The Influence of Motivation and Service Quality Towards Customer Satisfaction - Rafiqi, Idham Ramdan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This study aims to determine the impact of motivation and service quality on the customer satisfaction of participants in the Jakarta Cheetahs After Hour program. The research adopts an explanatory approach employing a quantitative method. Non-probability sampling techniques, specifically the purposive sampling method, were utilized, and the sample comprised 200 respondents. The inclusion criteria for respondents were a minimum age of 17 years and current or past participation in the Jakarta Cheetahs After Hour program. Measurement of items in the questionnaire was conducted using the Likert scale, assigning scores from 1 to 5. The Statistical Package for the Social Sciences (SPSS) was employed for the validity test, reliability test, and classical assumption test. Data analysis techniques included the multiple linear regression test and the coefficient of determination test. Hypothesis testing in this study involved partial hypothesis testing. The findings of this study indicate that the variable of Motivation (X1) has a positive influence on Customer Satisfaction (Y). Additionally, Service Quality (X2) was found to significantly impact Customer Satisfaction (Y). Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh motivasi dan kualitas pelayanan terhadap kepuasan pelanggan Partisipan Jakarta Cheetahs After Hour. Jenis penelitian ini merupakan explanatory research dengan metode kuantitatif. Penelitian ini menggunakan teknik nonprobability sampling dengan metode purposive sampling dan menggunakan sampel sebanyak 200 responden. Kriteria yang dibutuhkan responden dalam penelitian ini adalah berusia minimal 17 tahun dan pernah atau sedang mengikuti Jakarta Cheetahs After Hour. Pengukuran yang digunakan sebagai nilai item pertanyaan dalam kuesioner adalah Likert scale dengan skor 1-5. Penelitian ini menggunakan Statistical Package for the Social Sciences (SPSS) untuk melakukan uji validitas, uji reliabilitas, dan uji asumsi klasik. Sedangkan teknik analisis data yang digunakan dalam penelitian ini adalah uji regresi linier berganda dan uji koefisien determinasi. Uji hipotesis yang dilakukan dalam penelitian ini adalah uji hipotesis secara parsial. Temuan penelitian ini menunjukkan bahwa variabel Motivasi (X1) berpengaruh positif terhadap Kepuasan Pelanggan (Y), sedangkan Kualitas Pelayanan (X2) berpengaruh signifikan terhadap Kepuasan Pelanggan (Y).